Woman of influence : 9 steps to build your brand, establish your legacy, and thrive - Miller, Jo (Jo Kay) (McGraw Hill-Ascent Audio, 2019)
Reinvent yourself as a woman of influence-and become the leader you were meant to be Have you ever felt like your organization's best-kept secret? Are you the go-to person for work that downplays your potential? Do you want to hone your leadership skills while still staying true to who you are? If you answered yes to any of these questions, or if your reputation as a standout contributor is not translating into career advancement, Woman of Influence is for you. With more than two decades of experience working with hundreds of thousands of women and clients including eBay, GM, Microsoft, and more, Be Leaderly CEO Jo Miller has the strategies, stories, and research to help women shift their focus from doing to leading. In Woman of Influence, she provides a practical, hands-on roadmap that walks you through 9 specific steps to build your brand, establish your legacy, and thrive. Each step is reinforced with self-assessments, inspiring exercises, and checklists that have been road-tested by tens of thousands of professional women.